Empowering Young Learners: Effects of Differentiation-Based Educational Curriculum and Literacy Engagement on Student Learning Outcomes in Elementary School Science - Adisti, Fatimia Lady; Mulyani, Petra Kristi (Jurnal Pendidikan MIPA, 2025)
This study examines the effect of implementing Indonesia's Educational Curriculum and literacy interest on grade IV students' Natural Science learning outcomes. The Indonesia's Educational Curriculum, which emphasizes independent and flexible learning, is expected to improve students' understanding and skills in Natural Science lessons. This study uses a quantitative approach with an ex post facto method. The population and sample in this study were all grade IV elementary school students in the same cluster, which amounted to 106 students. Data collection techniques using documentation and closed questionnaires with a Likert scale with four answer options. Documentation in this study is in the form of natural science learning outcomes of elementary school students obtained during the end-of-semester assessment. The data analysis technique uses the t-test, f-test, and the coefficient of determination test.  Based on t-test calculations, Indonesia's Educational Curriculum results are sig. 0.000 <0.05 and literacy interest sig. 0.042 <0.05, which indicates that both Indonesia's Educational curriculum and learning literacy have a significant effect on Natural Science learning outcomes. In the F test, the sig value was obtained. 0.000 <0.05 indicates that Indonesia's Educational Curriculum and Literacy Interest variables simultaneously affect Natural Science Learning Outcomes. The coefficient of determination test results obtained the adjusted R square value of 0.748, which indicates that the independent variable affects the dependent variable by 73.1%, which means that this regression model is effective. Based on the overall final test results of the data analysis used, it is known that there is a positive influence between the two variables.      Keywords: indonesia’s educational curriculum, literacy interest, learning outcomes, natural science.